2020
DOI: 10.1371/journal.pone.0230623
|View full text |Cite
|
Sign up to set email alerts
|

Screening efficiency of the Mood and Feelings Questionnaire (MFQ) and Short Mood and Feelings Questionnaire (SMFQ) in Swedish help seeking outpatients

Abstract: Background To evaluate screening efficiency and suggest cutoffs for parent and child Mood and Feelings Questionnaire (MFQ) and the short version (SMFQ) in unselected help seeking childand adolescent psychiatric outpatients for subgroups of 6-12 versus 13-17 year olds and boys versus girls. Method Eligible for inclusion were newly admitted outpatients age 6-17 years (n = 5908) in four Swedish child-and adolescent psychiatry clinics. They were prompted consecutively and n = 307 accepted a specific day for assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 35 publications
3
30
1
1
Order By: Relevance
“…A score of 12 or higher may indicate the presence of clinically relevant depressive symptoms in the respondent 15 . Suggested cut-offs on the SMFQ self-report have been divergent with cut-offs ranging from 4–5 in studies with just fair AUC and younger subjects to a high of 10–12 in studies with good AUCs and older subjects 16 .…”
Section: Methodsmentioning
confidence: 99%
“…A score of 12 or higher may indicate the presence of clinically relevant depressive symptoms in the respondent 15 . Suggested cut-offs on the SMFQ self-report have been divergent with cut-offs ranging from 4–5 in studies with just fair AUC and younger subjects to a high of 10–12 in studies with good AUCs and older subjects 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Good to excellent internal consistency was found in the current sample ( α = 0.91). To divide the sample into depressed and non-depressed, the SMFQ scores were dichotomized to above clinical cut-off ( n = 163) and below clinical cut-off ( n = 150), applying a cutoff score of ≥12 for girls and ≥6 for boys, according to criteria suggested by Jarbin et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…Depression below clinical cut-off a (n = 150) Jarbin et al (2020). β, standardized beta; GAD, generalized anxiety disorder; OCD, obsessive compulsive disorder; SAD, separation anxiety disorder; SCAS, spence children's anxiety scale; SMFQ, short mood and feelings questionnaire; SoAD, social anxiety disorder; *p < 0.05, **p < 0.01, ***p < 0.001.…”
Section: Full Sample (N = 313)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by findings from studies in help-seeking adolescents. Jarbin et al (2020) suggested a lower cut-point for boys (≥6) compared to girls (≥12) and Thabrew et al (2018) suggested a cut-point of ≥12 for boys and ≥13 for girls. It is not clear to what extent age or puberty are responsible for the sex differences in cut-points.…”
Section: Discussionmentioning
confidence: 99%